Penerapan Rangkaian Simulasi Terintegrasi Untuk Efisiensi Penggunaan Modul Praktikum Mikrokontroler dan Interfacing - Anggara Nasution; Era Madona; Muhammad Irmansyah (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
The purpose of the design and application of the ATMEGA8535 microcontroller system simulation circuit is minimize the damage of the practicum module, helping students improve their understanding of practicum goals through maximum frequency of practices. Every year damage the practicum module avr8535 increased. Based on the analysis, the damage of this module is mostly caused by the damage of the main component, namely the IC ATMEGA8535. This happen because a maximum of program downloading to the IC ATMEGA8535 is 1000 times and this ability can even be less if the operation procedure of the module is incorrect. This simulation software utilizes the facilities contained in the proteus software. The steps to make this simulation circuit are doing the needs analysis, designed the basic circuit, ouput circuit, input circuit, and ADC circuit. The test results show all units of the circuit can run according to the practicum module. This simulation circuit has been implemented in microcontroller practicum activities and interfacing as companion software. There was a decrease in module damage of 57.60% after the implementation of simulation circuit. With this simulation software programs that have been created can be loaded first into a simulations circuit, so they can extend the life time of the practicum module and can help lecturers in developing lecture material and maximize the understanding of learning for students through practical activities.